2003
DOI: 10.1074/jbc.m212803200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Raf through Phosphorylation and N Terminus-C Terminus Interaction

Abstract: The Raf family of serine/threonine kinases is highly conserved in structure. There are three conserved regions (CR) 1 in Raf kinases, CR1, CR2, and CR3 (1). CR1 contains the Ras binding domain (RBD) and the cysteine-rich domain (CRD), and both bind the activated small GTPase Ras (2, 3). CR2 is serine/threonine-rich, and CR3 is the catalytic kinase domain and contains several activating phosphorylation sites. Activated Ras binds to CR1 and recruits Raf to the plasma membrane, which is necessary for Raf activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 30 publications
(29 reference statements)
7
86
0
1
Order By: Relevance
“…Our model (Figure 9a), similar to that suggested by Mercer and Pritchard (2003), is consistent with recent studies showing that the negatively charged N-region of Raf-1 relieves autoinhibition by the N-terminal moiety owing to its reduced affinity towards a CR3 with a charged N-region (Cutler et al, 1998;Tran and Frost, 2003). However, we accept that similar experiments led to the alternative conclusion that the charged N-region induces a conformational change that does not affect the interaction between N-and C-terminal moiety but renders the CR3 resistant to the autoinhibition imposed by the N-terminal moiety (Chong and Guan, 2003). Furthermore, while our manuscript was in preparation, Tran et al (2005) reported that introduction of the Regulation of B-Raf signalling T Brummer et al S446A mutation into the isolated CR3 increased the affinity of this region towards the isolated N-terminal domain of B-Raf (Tran et al, 2005).…”
Section: Regulation Of B-raf Signallingmentioning
confidence: 82%
“…Our model (Figure 9a), similar to that suggested by Mercer and Pritchard (2003), is consistent with recent studies showing that the negatively charged N-region of Raf-1 relieves autoinhibition by the N-terminal moiety owing to its reduced affinity towards a CR3 with a charged N-region (Cutler et al, 1998;Tran and Frost, 2003). However, we accept that similar experiments led to the alternative conclusion that the charged N-region induces a conformational change that does not affect the interaction between N-and C-terminal moiety but renders the CR3 resistant to the autoinhibition imposed by the N-terminal moiety (Chong and Guan, 2003). Furthermore, while our manuscript was in preparation, Tran et al (2005) reported that introduction of the Regulation of B-Raf signalling T Brummer et al S446A mutation into the isolated CR3 increased the affinity of this region towards the isolated N-terminal domain of B-Raf (Tran et al, 2005).…”
Section: Regulation Of B-raf Signallingmentioning
confidence: 82%
“…338 , and substitution of this site with alanine precludes Raf-1 activation by physiologic stimuli (34 -39). Phosphorylation of this site contributes to Raf-1 activation by blocking the ability of the Nterminal autoinhibitory domain to negatively regulate Raf-1 catalytic activity (28,29). Because this residue is conserved among Raf family members (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, the activation requirements of B-Raf are similar to those of Raf-1 because Raf-1 must also bind to Ras and requires phosphorylation of sites within the activation loop of its catalytic domain (Thr 491 and Ser 494 ) (27). However, full activation of Raf-1 also requires phosphorylation of Ser 338 and Tyr 341 , which lie outside the catalytic domain and contribute to the Raf-1 activation mechanism by blocking the actions of the autoinhibitory do-main (28,29). Interestingly, the residues in B-Raf corresponding to Tyr 340 and Tyr 341 in Raf-1 are substituted with aspartic acids, and Ser 445 , which corresponds to Ser 338 in Raf-1, appears to be constitutively phosphorylated in COS and PC12 cells (30).…”
mentioning
confidence: 99%
“…3). Phosphorylation of these activating sites by an unknown, membrane-localized kinase is thought to be a late step in Raf activation (43). Both LIN-45(AA) and LIN-45(ED) mutants can induce a Muv phenotype, when expressed as a transgene (32).…”
Section: Resultsmentioning
confidence: 99%
“…The analogous residues in mammalian Raf proteins serve as docking sites for the 14-3-3 chaperone, which inhibits translocation of Raf to the membrane (42). Dephosphorylation of these inhibitory sites by PP2A is thought to be an early step in Raf activation (43). The second form of activated LIN-45 Raf, LIN-45(ED), contains negatively charged residues that mimic activating phosphorylation within the activation loop of the kinase domain (32) (Fig.…”
Section: Resultsmentioning
confidence: 99%